2009
DOI: 10.1007/s10641-009-9542-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal foraging and piscivory by sympatric wild and hatchery-reared steelhead from an integrated hatchery program

Abstract: We compared the diet of hatchery-reared steelhead produced from an integrated hatchery program as emigrating spring smolts and nonmigrating hatchery residuals to their sympatric wild counterparts. Our results suggest that there is a potential for hatchery fish to affect wild steelhead populations due to dietary overlap and subyearling salmonid predation; however, relative ecological risk did not increase as steelhead delayed or forwent emigration. Predation by hatchery smolts was related to release timing, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Regardless, the ecological implications of hatchery fish in the three Hood Canal streams will come primarily from fish greater than 200 mm, which were also more abundant than small residuals in each of the three streams. The incidence of predation by steelhead smolts and Proportion of population N=100 for each of three raceways (1-3) of age-1 smolts and each of two raceways (4 and 5) of S2 smolts summer residuals on juvenile salmon is typically very low (Sharpe et al 2008;Simpson et al 2009), but in rare cases can be a substantial source of mortality for juvenile salmon (Naman and Sharpe 2011). Interference competition between hatchery and wild juvenile salmonids is strongly determined by relative body size, and intraspecific competition appears to be more intense than interspecific competition (Tatara and Berejikian 2011).…”
Section: Body Size Maturity and Residualismmentioning
confidence: 99%
“…Regardless, the ecological implications of hatchery fish in the three Hood Canal streams will come primarily from fish greater than 200 mm, which were also more abundant than small residuals in each of the three streams. The incidence of predation by steelhead smolts and Proportion of population N=100 for each of three raceways (1-3) of age-1 smolts and each of two raceways (4 and 5) of S2 smolts summer residuals on juvenile salmon is typically very low (Sharpe et al 2008;Simpson et al 2009), but in rare cases can be a substantial source of mortality for juvenile salmon (Naman and Sharpe 2011). Interference competition between hatchery and wild juvenile salmonids is strongly determined by relative body size, and intraspecific competition appears to be more intense than interspecific competition (Tatara and Berejikian 2011).…”
Section: Body Size Maturity and Residualismmentioning
confidence: 99%
“…Simpson et al (2009) found that hatchery steelhead smolts released in mid-April consumed significantly more subyearling salmonids than those released in May. For potential prey species like wild steelhead that emerge from spawning gravels in April and May, reducing the spatial overlap of predator and prey may be the most effective way to reduce the predation rate.…”
Section: Managing the Predation Ratementioning
confidence: 99%
“…Other than the research performed by Hawkins and Tipping (1999) and Simpson et al (2009), all of the documents were contract reports or other forms of grey literature and had not been published at the time of this review. Two of the studies examined predation by yearling coho salmon (Oncorhynchus kisutch), while twelve examined predation by hatchery steelhead (O. mykiss).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations